Air Spy: The Story of Photo Intelligence in World War II - Babington-Smith C. (New York Harper & Brothers Publishers, 1957)
The book narrates the extraordinary efforts in reconnaissance based on aerial imagery, focusing on the photographers and intelligence operatives, as well as their contributions to key battles and military operations. It combines historical analysis with personal stories of heroes and details of technological advancements in photo intelligence during the war.
Keywords: 355